The Effect of the Pressure on the Discharge of Multiphase Oil Pipeline - Ismayilova, F.B.; Iskandarov, E.Kh. (Herald of Azerbaijan Engineering Academy, 2021)
In the article, it was attempted to model laminar and turbulent flows for multiphase mixtures at different pressure values, taking into account changes in the degree of compression. Taking into account the nature of the pressure drop along the pipeline, mathematical expressions characterizing the pressure-dependent variation of flow in the pipeline for laminar and turbulent flows have been obtained. Analysis of the obtained expressions showed that the impact of pressure on the discharge of oil pipelines in both turbulent and laminar modes of multiphase flows is quite high, and this effect can increase up to 60%, depending on the average pressure in the pipeline.